Teaching and learning for adult skill acquisition : applying the Dreyfus and Dreyfus model in different fields - Silva Mangiante, Elaine M.; Peno, Kathy; Northup, Jane (Emerald Publishing Limited : INFORMATION AGE PUBLISHING, INC., 2021)
"The book, Teaching and Learning for Adult skill Acquisition: Applying the Dreyfus and Dreyfus Model in Different Fields, will fill a unique niche in the field of adult, higher, and workforce education and offer a current volume for scholars and practitioners based on both empirical studies and practice-based research on adult skill acquisition and development. Dreyfus and Dreyfus (1980, 1988, 2004) developed the novice to expert model of skill acquisition that illustrates growth over the course of a person's career in a particular domain. The skill model highlights a learner's movement across six levels of skill development: novice, advanced beginner, competent, proficient, expert, and mastery. This book will present examples of the application of the Dreyfus and Dreyfus model in different fields (i.e., health care, education, law enforcement, business, serious gaming, military, ethics training, etc.) providing insight into how practitioners can develop their skills in their particular domains and how educators can promote this development. This collection will be appropriate for a wide variety of professors, researchers, practitioners, and students in the field of adult, higher, and workforce education"-- Provided by publisher.
Keywords: Adult learning.; Adult education -- Study and teaching.; Mentoring in education.; Workplace literacy.; Career development.; Education -- Adult & Continuing Education.; Adult education, continuous learning.; elektronické knihy; electronic books